Taxonomy and systematics are key to biological information: Arabidopsis, Eutrema (Thellungiella), Noccaea and Schrenkiella (Brassicaceae) as examples - Koch, Marcus A.; German, Dmitry (Frontiers in Plant Science, 2013)
Taxonomy and systematics provide the names and evolutionary framework for any biological study. Without these names there is no access to a biological context of the evolutionary processes which gave rise to a given taxon: close relatives and sister species (hybridisation), more distantly related taxa (ancestral states), for example. This is not only true for the single species a research project is focusing on, but also for its relatives, which might be selected for comparative approaches and future research. Nevertheless, taxonomical and systematic knowledge is rarely fully explored and considered across biological disciplines. One would expect the situation to be more developed with model organisms such as Noccaea, Arabidopsis, Schrenkiella and Eutrema (Thellungiella). However, we show the reverse. Using Arabidopsis halleri and Noccaea caerulescens, two model species among metal accumulating taxa, we summarize and reflect past taxonomy and systematics of Arabidopsis and Noccaea and provide a modern synthesis of taxonomic, systematic and evolutionary perspectives. The same is presented for several species of Eutrema s. l. and Schrenkiella recently appeared as models for studying stress tolerance in plants and widely known under the name Thellungiella.